Plasmonics Around the Clock: "Hot" in Plasmonics: Temperature‐Related Concepts and Applications of Metal Nanostructures (Advanced Optical Materials 1/2020). Issue 1 (3rd January 2020) - Kuppe, Christian; Rusimova, Kristina R.; Ohnoutek, Lukas; Slavov, Dimitar; Valev, Ventsislav K.
Abstract : Light shining on gold nanoparticles triggers a stream of physical processes, across three timescales. Femtosecond processes yield applications in advanced microscopic imaging, solar cells and water splitting. Picosecond processes result in nano metalworking. Nanosecond processes lead to photothermal therapy, denser magnetic storage and nanorobotics. The Review by Ventsislav K. Valev and co‐workers (article number 1901166 ) provides a survey of these exciting areas of research. The cover art is created by Ventsislav K. Valev and Alex Murphy.